Non-surgical treatment of hallux valgus: practices of Brazilian foot and ankle specialists - Soares Baumfeld, Tiago; Caldas Couto, Caio; Zambelli, Roberto de Almeida Pinto; Baumfeld, Daniel Soares; Nunes, Gustavo Araújo; Santos, Alexandre Leme Godoy dos (Journal of the Foot & Ankle, 2024)
Objective: This study aims to analyze how Foot and Ankle specialists in Brazil approach Hallux Valgus conservatively. Methodology: An online questionnaire was used to assess the practices adopted. The results were analyzed, and proportions were calculated to determine if there is a common treatment pattern or variations. Results: There is a clear preference among Brazilian foot and ankle specialists regarding conservative treatment. Primary emphasis is placed on footwear adjustment and lifestyle modification, followed by the use of silicone protectors. The utilization of custom-made and prefabricated orthoses is less common compared to the preference for these methods among specialists worldwide. The literature tends to indicate that non-surgical methods primarily provide symptomatic relief to patients, with a negligible delay in the progression of the comorbidity. Conclusion: For those opting for conservative treatment, there is a consensus in Brazil regarding the change of footwear and lifestyle, aligning with the preference of experts worldwide. Level of Evidence III; Retrospective comparative study.